+0  
 
0
66
1
avatar

The difference of the roots of the quadratic equation $x^2 + bx + c = 0$ is $|b - 2c|$. If $c \neq 0$, then find $c$ in terms of $b$.

 

TYSM!

 Feb 19, 2021
 #1
avatar+117978 
+1

The  difference  of  the  roots     = sqrt  ( b^2  - 4ac) =  sqrt   ( b^2  - 4c)

 

And   l b - 2c  l    can be written  as   sqrt [ (b - 2c)^2   ]

 

This implies that

 

b^2   - 4c  =   ( b  - 2c)^2

 

b^2  - 4c  = b^2  - 4bc  + 4c^2

 

-4c  =  -4bc + 4c^2

 

c  =  bc  - c^2

 

c^2  +  c  =  bc

 

c + 1    = b

 

c   =   b   - 1

 

 

cool cool cool

 Feb 19, 2021

43 Online Users

avatar
avatar
avatar
avatar